Food Insecurity and Cardiometabolic Conditions: a Review of Recent Research - Te Vazquez, Jennifer (Curr Nutr Rep, 2021)
PURPOSE OF REVIEW: To understand recent literature that examines associations between food insecurity and cardiometabolic conditions and risk factors. We included original research, systematic reviews, and meta-analyses on the topic of food insecurity and cardiometabolic risk published from January 1, 2017, to December 31, 2020. Editorials, perspectives, and case reports were excluded. After the initial search, 3 reviewers selected studies for inclusion based on relevance and methods. Ultimately, fifty studies were included. RECENT FINDINGS: We included 35 studies of adults (20 cross-sectional observational studies, 5 longitudinal observational studies, 5 interventional studies, and 5 meta-analyses/reviews). In adults, food insecurity is associated with greater prevalence of overweight/obesity (especially for women). It is also associated with hypertension, diabetes (including worse glycemic control and more diabetes complications), coronary heart disease, congestive heart failure, stroke, and chronic kidney disease. We included 15 studies of children (11 cross-sectional observational studies and 4 longitudinal observational studies). In children, findings were more nuanced, and in particular, many studies did not find an association between food insecurity and overweight/obesity. However, authors noted that these conditions may not have had time to develop. With notable exceptions, many studies were cross-sectional, and there were few interventions. SUMMARY: There is a robust association between food insecurity and cardiometabolic conditions and risk factors in adults, but the picture is less clear in children. Overt cardiometabolic clinical conditions develop more rarely in children, but childhood experiences may set a trajectory for worse health later in life. Detailed life course epidemiologic studies are needed to better understand this relationship. Future interventions should examine how to reduce the prevalence of food insecurity, and how best to improve health for those who experience food insecurity.